2010
DOI: 10.1007/s10661-010-1755-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial characteristics at the monitoring plots on windthrow areas of the Tatra National Park (Slovakia): their assessment as environmental indicators

Abstract: This study focused on the responses of soil microorganisms to different management regimes on disturbed windthrow areas. Microbial parameters potentially serving as indicators of environmental changes within a long-term monitoring of forest development after large-scale disturbance events were assessed. Basal and substrate-induced respiration, N mineralisation, catalase activity, microbial biomass as well as functional diversity based on Biolog assay were determined in soil samples from three disturbed plots a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…( (Gömöryová et al 2011). Soil profile: 0-2 cm litter (spruce needles), 2-6 cm humus layer, 6-10 (15) cm dark brown mineral layer, under 15 cm and lower transition to paler mineral layer with stones.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…( (Gömöryová et al 2011). Soil profile: 0-2 cm litter (spruce needles), 2-6 cm humus layer, 6-10 (15) cm dark brown mineral layer, under 15 cm and lower transition to paler mineral layer with stones.…”
Section: Methodsmentioning
confidence: 99%
“…In EXT stands, a large part has been overgrown by weeds, especially Calamagrostis villosa (Chaix) and Avenella flexuosa (L.) (Gömöryová et al 2011). Soil profile: 0-2 cm litter (spruce needles), 2-6 cm humus layer, 6-10 (15) cm dark brown mineral layer, 10-15 cm transition to grey or pale brown mineral layer with stones.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Šoltés et al (2010) examined successional dynamics of vegetation in these windthrown stands. The windthrow was found to have led to a general decrease of soil microbial biomass and activity at disturbed plots (Gömöryová et al 2011). It was additionally found that the disturbance of forest soil and vegetation increased abundance of nematode communities in stands damaged by fire and stands left to natural succession, mostly due to colonizers or rstrategist species (Čerevková & Renčo 2009).…”
Section: Introductionmentioning
confidence: 96%